How High Should Paternity Index Be for Reliable Identification of War Victims by DNA Typing? - Biruš, Ivan; Marcikić, Mladen; Lauc, Davor; Džijan, Snježana Lauc, Gordan (2003)
Statistical and logical analysis of the significance of genetic matches between skeletal remains and relatives of missing persons in the process of identification of war victims by DNA typing. DNA was isolated from bone and blood samples and typed using AmpFLSTR Profiler, Profiler Plus and Identifiler kits. Novel mini-haplotype analysis was developed that compares matches in all three-loci combinations of alleles was developed and used to study inbreeding in the group of 295 unrelated individuals. While comparing 98 skeletal remains exhumed in the process of identification of war victims in Croatia with over 3, 000 genotypes of relatives of missing persons we observed 20 cases of 14-loci matches and 5 cases of 15-loci matches between unrelated people. We hypothesized that this unexpectedly high number of false matches might be a consequence of local inbreeding and supported this hypothesis with very low correlation between the probability of a genotype and the number of matching genotypes in the database (R2 = 0.36). Further support for the hypothesis was obtained by the analysis of mini-haplotypes that revealed up to 90% overrepresentation of some mini-haplotypes. STR DNA typing is the "golden standard" of human identification, but evidential value of a genetic match can be easily misinterpreted and careful use of statistical methods is essential for the proper evaluation of laboratory results. Whenever possible, multiple relatives should be analyzed, and other evidence based on the information about time, place and other conditions of disappearance, as well as anthropological and other "classical" forensic data should always be put together and compared before any final decision about the identity is made.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG